2004
DOI: 10.3171/ped.2004.100.2.0163
|View full text |Cite
|
Sign up to set email alerts
|

Failure of autologous bone—assisted cranioplasty following decompressive craniectomy in children and adolescents

Abstract: The use of autologous bone to reconstruct skull defects in pediatric patients after decompressive craniectomy is associated with a high incidence of bone resorption. The use of autologous bone should be reevaluated in light of the high rate of reoperation in this pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
252
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(267 citation statements)
references
References 0 publications
8
252
2
5
Order By: Relevance
“…In this method, there is destruction of bone proteins so the bone flap does not revitalize, and chances of resorption and SSI after cranioplasty is more [20][21][22]. Studies [9] have documented that implanted bone flaps which are larger than 12 cm and have been preserved for more than 6-9 months (delayed cranioplasties), have a tendency for aseptic resorption resulting in deficiencies at the edges of the bone flap following reimplantation [23], which becomes evident clinically as well as radiographically. Studies have also documented that the longer the delay in cranioplasty, the greater are the chances of autogenous bone flap resorption as well as SSI following cranioplasty [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, there is destruction of bone proteins so the bone flap does not revitalize, and chances of resorption and SSI after cranioplasty is more [20][21][22]. Studies [9] have documented that implanted bone flaps which are larger than 12 cm and have been preserved for more than 6-9 months (delayed cranioplasties), have a tendency for aseptic resorption resulting in deficiencies at the edges of the bone flap following reimplantation [23], which becomes evident clinically as well as radiographically. Studies have also documented that the longer the delay in cranioplasty, the greater are the chances of autogenous bone flap resorption as well as SSI following cranioplasty [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Although autografting, that is, either reimplantation of the excised bone flap [6,7], or transfer of cortical, cancellous or corticocancellous bone from any anatomic site to the defect site in the same subject, is obviously the best choice owing to the lack of immune or foreign body reactions, absence of a risk of transmission of disease, and the potential of the graft to be incorporated as biologically active and dynamic living tissue it has certain inherent limitations and disadvantages. Bone flap/graft resorption and infection [8,9], donor site morbidity, inadequate quantity of graft harvestable to bridge large cranial defects, prolonged intra-operative time, intraoperative blood loss and requirement of transfusions, need for surgical expertise and delayed post operative recovery [10] are definite drawbacks of autografting. Advanced age, presence of comorbidities, poor general condition of the patient, difficulties with bone flap storage, acute case scenarios and anatomical constraints can lead to difficulty in autografting or to the loss of the excised bone flap in a large number of cases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, using autologous bone for cranioplasty has been suggested to result in a high incidence of bone resorption, particularly in the pediatric population: as high as 50% in that population, versus 0%-7% in the adult population. 8,20 Similarly, it has been reported to result in a high rate of surgical site infection: an average of 7.9% across 18 studies, according to a recent large-scale systematic review of postcranioplasty complications in adult patients. 20 This result suggests that surgical site infection is a significant cause of morbidity following cranioplasty in adults.…”
mentioning
confidence: 99%
“…Cranioplasty is subsequently required to restore cosmesis and to avoid physiological disturbances that may result from the cranial defect. 8,19 Repair of the skull defect using the original autologous bone has been advocated by some, since it maintains the proper contour of the skull, avoids introducing foreign material, 8 and can result in bone reintegration with the native calvaria during normal growth. However, using autologous bone for cranioplasty has been suggested to result in a high incidence of bone resorption, particularly in the pediatric population: as high as 50% in that population, versus 0%-7% in the adult population.…”
mentioning
confidence: 99%
“…However, Grant et al reported a high rate (50%) of symptomatic bone resorption (requiring another surgery) in 40 cases of children and teenagers submitted to DC with bone stored in the bone bank 17 . Other techniques can be associated to an even higher resorption rate such as autoclaving the bone, once denaturation of proteins responsible for bone growth occurs 18 .…”
Section: Discussionmentioning
confidence: 99%